KAJIAN KEAMANAN DAN KENYAMANAN FASILITAS PEDESTRIAN DI JALAN OTTO ISKANDARDINATA - Rohana, Asep; Ayu Oktaviani (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2022)
Pedestrians are sidewalks that are intended for pedestrians to enjoy the feel ofurban buildings and City / Regency parks. Pedestrians are a key indicator for theadvancement of civilization and future city development. In fact, many pedestrianshave become parking lots for cars or motorcycles, and have become areas for streetvendors selling their wares. This creates a feeling of discomfort for pedestrians andtourists who want to take a walk to enjoy urban and rural areas, City development isvery influential on population factors and on the other hand it also depends on thecarrying capacity of land and regional capabilities, in terms of financing or budgetcosts.